Multi-drug-resistant tuberculosis (MDR-TB): Current situation in South Africa - Gboyega A Ogunbanjo (South African Family Practice)
Multi-drug-resistant tuberculosis (MDR-TB) is a form of tuberculosis (TB) infection which is resistant to treatment with at least two of the most powerful first-line anti-TB drugs, namely isoniazid and rifampicin. Globally, MDR-TB caused an estimated 480 000 new TB cases and 250 000 deaths in 2015 and accounted for 3.3% of all new TB cases worldwide.1 MDR-TB, or rifampicin-resistant TB, causes 3.9% of new TB cases and 21% of previously treated TB cases, and most MDR-TB cases occur in South America, southern Africa, India, China, and the former Soviet Union.1